1992
DOI: 10.1115/1.2906600
|View full text |Cite
|
Sign up to set email alerts
|

Separating Hydrogen From Coal Gasification Gases With Alumina Membranes

Abstract: Synthesis gas produced in coal gasification processes contains hydrogen, along with carbon monoxide, carbon dioxide, hydrogen sulfide, water, nitrogen, and other gases, depending on the particular gasification process. Development of membrane technology to separate the hydrogen from the raw gas at the high operating temperatures and pressures near exit gas conditions would improve the efficiency of the process. Tubular porous alumina membranes with mean pore radii ranging from about 9-22 Å have been fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In the current context, in situ capture of CO 2 not only provides a chance to sequester the greenhouse gas, but also increases the conversion to and the purity of the H 2 stream by removing the thermodynamic limitations at a given condition. Thus, separation of the CO 2 and H 2 needs to be achieved. Separation of H 2 from the coal gasification products also supports existing H 2 markets (such as refineries and power production) and makes a H 2 economy a distinct possibility.…”
Section: Introductionmentioning
confidence: 99%
“…In the current context, in situ capture of CO 2 not only provides a chance to sequester the greenhouse gas, but also increases the conversion to and the purity of the H 2 stream by removing the thermodynamic limitations at a given condition. Thus, separation of the CO 2 and H 2 needs to be achieved. Separation of H 2 from the coal gasification products also supports existing H 2 markets (such as refineries and power production) and makes a H 2 economy a distinct possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have shown that if 90% CO, abatement is to be achieved then a separation factor of about 200 might be required, and therefore some mechanism other than simple diffusion will need to dominate the membrane performance. Research into membranes with a high selectivity for hydrogen is making progress in this area (Egan et al, 1991). The overall performance of a power plant incorporating this concept has been assessed based on the assumption that a sufficiently selective membrane can be developed, operating with a 10 bar pressure drop.…”
Section: Membrane Separation Systemmentioning
confidence: 99%
“…Hydrogen incorporation into SiO 2 films grown by chemical vapor deposition (CVD) techniques is the main impediment to obtain as-deposited films with structural characteristics close to those obtained by the thermal oxidation of silicon at high temperatures . Nonbridging SiOH and SiH groups break the network continuity and thus are generally associated with the presence of porous structures in the oxide matrix. Parasitic capacitance, low breakdown field, and high dielectrical permittivity are frequent nondesirable characteristics in hydrogenated oxides. , Hydrogen incorporation results also in low refractive indexes for SiO 2 -based optical coatings, increased diffuse reflection, and important losses in optical fiber transmissions. ,, In addition, SiO 2 -based ceramic membranes for hot gas separation in industrial processes under aggressive conditions, such as those imposed by coal gasification cycles, are required to be thermally and chemically stable. , Obviously, the requirements for all these applications are compromised by the incorporation of SiOH and SiH groups into the oxide matrix. , …”
Section: Introductionmentioning
confidence: 99%
“…2,4,[8][9][10] In addition, SiO 2 -based ceramic membranes for hot gas separation in industrial processes under aggressive conditions, such as those imposed by coal gasification cycles, are required to be thermally and chemically stable. 11,12 Obviously, the requirements for all these applications are compromised by the incorporation of SiOH and SiH groups into the oxide matrix. 2,13 Despite these disadvantages, hydrogen incorporation into SiO 2 can be exploited to prepare porous nanostructured materials with interesting applications in the domain of gas and liquid separation 14 as well as in the manufacture of ultra-large-scale integrated solid-state devices.…”
Section: Introductionmentioning
confidence: 99%